Modified Direct Transfer Coping Technique for Making Impression of Closely Placed Implants - Kunwarjeet Singh (Journal of Dentistry And Oral Implants, 2019)
The main purpose of the impression is to record and transfer the relationship between implants and to reproduce this relationship as accurately as possible. But, Unplanned placement of the implants may result in close approximation of the implants, thereby posing tough challenge to the restorative dentist, to first accurately record the impression and later on fabricate the prosthesis with satisfactory esthetics and function. This article presents a modified direct impression coping procedure for precise making of impression of closely placed implants which otherwise may be difficult to replicate the exact position of the implants by conventional direct or indirect technique.
Keywords: Implants